Introduction of An Indirect Haemagglutination Test as a Rapid Diagnostic Method in Comparison With ELISA Using Antigen B for Diagnosis of Human Hydatid Disease - A Vatankhah; M Assmar; MA Shokrgozar; SA Taghavi Hoseini; AR Esmaeili Rastaghi (Tehran University of Medical Sciences, 2004)
Early diagnosis of human hydatid disease by detecting the specific antibodies in patients' sera is considered as an important step in treatment of infection. But the diagnostic efficiencies of assays greatly depend on the characteristics of antigen that is used and various conditions in performance. In present study, we tried to standardize an indirect haemagglutination test, using antigen B for diagnosis of hydatid disease. Sera from 80 patients with surgically confirmed hydatidosis and 40 sera from healthy donors were examined. To detect the cross-reactant antibodies, 53 sera from patients with other parasitic infectious and diseases were applied in this study. IHA was performed with sheep RBC that was sensitized by various concentrations of crude antigen and antigen B. The best results were obtained by IHA with applying antigen B (10μg/ml) for 40 min at 37˚C or 60 min at room temperature. Diagnostic value of antigen B (sensitivity 93.75%, specificity 100% and efficiency 97.12%) was significantly higher than related value of crude antigen (sensitivity 65%, specificity 100% and efficiency 83.81%) in IHA under the optimum condition. Sensitivity and specificity of ELISA using crude antigen (10μg/ml) were obtained 80% and 94.62%, respectively. Corresponding values of ELISA using antigen B were also obtained as 72.5% and 98.92%, respectively. It is suggested that the IHA, as a serological assay, is a valuable method with high diagnostic efficiency for serodiagnosis of hydatid disease, when is performed by purified antigen B. It is a rapid diagnostic assay with any needs neither for expensive instruments nor expert personnel so is useful for seroepidemiological studies and field trial in endemic areas.